L’etica materiale dei valori di Max Scheler. Tra gnoseologia e teoria dell’a-priori - Tumminelli, Angelo (Filosofia Morale/Moral Philosophy, 2023)
The paper is focused on the moral theory developed by Max Scheler in the work “The Formalism and Material Ethics of Values” (1913/1916). After considering the essential philosophical aspects of the material ethics of values, the author focuses on the role that Scheler attributes to a-priori knowledge, with reference to the intuition of moral values in the emotional acts of the human person. Therefore, the author analyses Scheler’s conception of the access to value through the emotional life and he reflects on the objective character of the moral value, considered by Scheler as an absolute phenomenological essence, in opposition to any form of relativism and ethical subjectivism.